Detection and sequencing of blaVEB-1 gene in clinical isolates of Proteus mirabilis Isolates from Baghdad City`s hospitals - Maysoon Munther Al-Hamando; Dimah Nazar Faraj; Lina Arjamand (World Journal of Experimental Biosciences, 2017)
In Present study, 25 clinical isolates of Proteus spp. of clinical samples, urine, wounds and burns collected from different hospitals in Baghdad city, all isolates were identified as Proteus mirabilis using different bacteriological media, biochemical assays and Vitek-2 system. It was found that 15 (60%) isolates were identifying as P. mirabilis. The susceptibility of P. mirabilis isolates to cefotaxime was 66.6 %, while to ceftazidime was 20%. Extended spectrum β-lactamses producing Proteus was 30.7 %. DNA of 5 isolates of P. mirabilis was extracted and detection for blaVEB-1 gene by using multiplex polymerase chain reaction (PCR). Results showed that the presence of this gene in all tested isolates, as an important indicator for increasing risk of extended spectrum beta lacatmases resistant P. mirabilis isolates against antimicrobial agents due to its spread recently in Middle and Far East of Asia. Sequencing of DNA nucleotides was carried out with automated sequencer (Macrogen/ Korea) and confirmed that 3 isolates of P. mirabilis have blaVEB-1 gene, while one isolate has blaVEB-3 gene.
Keywords: Proteus mirabilis, blaVEB-1 gene, beta-lactamases, EXBLs enzymes.